Pengaruh Varietas dan Berat Umbi terhadap Viabilitas Bibit Bawang Merah (Allium ascalonicum L.) - Mulyani, Iluh Sri; Darmawati, Ida Ayu Putri; Mayun, Ida Ayu (Agrotrop : Journal on Agriculture Science; Vol 14 No 2 (2024), 2024)
The Effect of Variety and Bulb Weight on the Viability of Shallot Seedlings ( Allium ascalonicum L.). The demand for shallots continues to increase so production needs to be increased, one of the efforts that can be made is to provide good quality seeds. Viability is a benchmark in determining seedling quality. Seedling viability can be influenced by variety and bulb weight. This study aims to determine the effect of variety and bulb weight on the viability of shallot seedlings ( Allium ascalonicum L.). The experimental design used is a completely randomized design (CRD) factorial pattern with two factors. The first factor is variety, namely Bali Karet, Biru Lancor, and Batu Ijo. The second factor is bulb weight, which is large (12-16 g), medium (8-12 g), and small (4-8 g). The research was conducted in the Greenhouse of the Experimental Garden of the Faculty of Agriculture, Udayana University, Denpasar from February to April 2023. The results showed that the variety treatment had a significant effect on the percentage of shoots. The highest percentage of shoots appeared in the Bali Karet variety which was 72.22%. The treatment of bulb weight has a very real effect on the viability of shallot seedlings. The highest viability is found in the weight of large bulb (12-16 g), namely the percentage of shoots appearing 73.33%, the time to appear shoots 5.95 days, shoot length 17.13 cm, root length 13.83 cm, and total dry weight of seedlings 0.74 g, and there is an interaction of varieties and bulb weight that has a very significant effect on shoot length and total dry weight of seedlings. The best treatment combination is found in the Bali Karet variety and the weight of large bulb (12-16 g), namely the highest shoot length and total dry weight of seedlings, namely 16.67 cm and 0.74 g.